Differences In the Types of Lexemes and Words Related To "Bread", Their Features in Lexicology - Ibatova Amira Shavkatovna (Genius Journals, 2022)
The article considers the "lexeme" as a unit of lexical meaning that exists regardless of the number of possible inflectional endings or the number of words, and the "word" as the main structural and semantic unit of the language, which serves for naming objects and their properties, phenomena, relations of reality, having a set of semantic, phonetic and grammatical features specific to the language. The concept of a lexeme is introduced in order to reflect the difference between a word as a system of grammatical forms or its separate word form and a word as a set of lexical and semantic variants that implement it. The meaning of the word reflects the general and at the same time essential features of the subject, learned as a result of people's social practice. Types, bread, forms, examples, varieties of lexemes and words in linguistics are also considered
Keywords: Bread; Language; Abstract; Term